Survivorship rates of adult Anolis mariarum (Squamata: Polychrotidae) in two populations with differing mean and asymptotic body sizes - Bock, Brian C.; Zapata, Ana María; Páez, Vivian P. (Papéis Avulsos de Zoologia, 2010)
We compared adult survivorships in two populations of the lizard Anolis mariarum with different mean and asymptotic body sizes to examine one prediction of age-specific mortality theory; that populations that experience higher adult mortality should exhibit earlier maturation and smaller adult body sizes. We used a maximum likelihood approach to evaluate different survivorship models and model-averaging to estimate survivorship and capture probabilities for each site and sex. Relative tail length did not affect survivorship rates of adults in these two populations, but body size was related to survivorship, with the largest individuals at the time of first capture having lower survivorship rates, so body size was included as a covariate in some of the models examined. Analyses revealed that males at both sites had higher survivorships than females, but there were no differences among the sites in survivorship rates or capture probabilities for either sex. The differences in body sizes documented for these sites still could represent life history adaptations to differences among the sites in mortality rates in the egg or juvenile stages of the life cycle, or may represent a case of phenotypic plasticity to differing environmental conditions, but they appear not to be related to differences in adult survivorships. The estimates of annual survivorships (11.7% to 21.2%) were high for a small, mainland Anolis, and this is the first report of survivorships of male anoles exceeding those of females.